RGD-dependent binding of TP508 to integrin αvβ3 mediates cell adhesion and induction of nitric oxide - Derkach, Dmitry N.; Wadekar, Subhagya A.; Perkins, Kim B.; Rousseau, Emma; Dreiza, Catherine M.; Cheung-Flynn, Joyce; Ramos, Heidi C.; Ugarova, Tatiana P.; Sheller, Michael R. (Thrombosis and Haemostasis, 2010)
P508, a 23-amino acid RGD-containing synthetic peptide representing residues 508 to 530 of human prothrombin, mitigates the effects of endothelial dysfunction in ischaemic reperfusion injury. The objective of this study was to investigate whether TP508 binds to members of the integrin family of transmembrane receptors leading to nitric oxide synthesis. Immobilised TP508 supported adhesion of endothelial cells and αvβ3-expressing human embryonic kidney cells in a dose- and RGD-dependent manner. Soluble TP508 also inhibited cell adhesion to immobilised fibrinogen. The involvement of αvβ3 was verified with function-blocking antibodies and surface plasmon resonance studies. Adhesion of the cells to immobilised TP508 resulted in an induction of phosphorylated FAK and ERK1/2. In endothelial cells, TP508 treatment resulted in an induction of nitric oxide that could be inhibited by LM609, an αvβ3-specific, function-blocking monoclonal antibody. Finally, TP508 treatment of isolated rat aorta segments enhanced carbachol-induced vasorelaxation. These results suggest that TP508 elicits a potentially therapeutic effect through an RGD-dependent interaction with integrin αvβ3.
Keywords: TP508; eNOS; nitric; oxide; endothelial; dysfunction; integrin